Penerapan Metode DMAIC untuk Minimalisasi Material Scrap pada Warehouse Packaging Marsho PT. SMART Tbk. Surabaya - Muhammad Habib Isna Nur Asnan; Fakhrina Fahma (Industrial Engineering, Faculty of Engineering, Universitas Sebelas Maret, 2019)
As one of the manufacturing companies engaged in food, PT SMART Tbk. Surabaya often having problem about the quality of materials stored in Warehouse Packaging Marsho which is often founded scrap materials. Based on the data from April 1st, 2017 to February 15th, 2015, the percentage of scrap material is increasing every month from 5% to 23%. The purpose of this research is to minimize the scrap materials in Warehouse Packaging Marsho PT. SMART Tbk. Surabaya using DMAIC method by implementing Define, Measure, Analyze, Improve, and Control stages. The results are the most dominant cause of scrap is the laziness of operator to place materials in accordance with the provisions (general batch). Thus, it is necessary to make improvements to minimize the scrap material by doing a routine briefing from PIC Area Warehouse Packaging Marsho before the operational activities begin.